2013
DOI: 10.1111/1462-2920.12177
|View full text |Cite
|
Sign up to set email alerts
|

The resolution and regeneration of a cointegrate plasmid reveals a model for plasmid evolution mediated by conjugation and oriT site‐specific recombination

Abstract: Cointegrate plasmids are useful models for the study of plasmid evolution if their evolutionary processes can be replicated under laboratory conditions. pBMB0228, a 17 706 bp native plasmid originally isolated from Bacillus thuringiensis strain YBT-1518, carries two nematicidal crystal protein genes, cry6Aa and cry55Aa. In this study, we show that pBMB0228 is in fact a cointegrate of two plasmids and contains two functional replication regions and two functional mobilization regions. Upon introduction into B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…This oriT recombination was likely mediated by the relaxase of the ICE, which is able to recognize and nick this sequence. Such oriT site-specific recombination has already been demonstrated for several canonical relaxases of plasmids (belonging to the MobF, MobP, MobC, and MobM families) (4,28,29) and has been suggested to occur in ICEs of the SXT/R391 family and for ICEclc (both encoding canonical relaxases of the MobH family) (30,31). This mechanism that enables creation of hybrid ICEs could thus also be mediated by relaxases of the noncanonical MobT family, which are related to rolling circle replication initiators and are found in ICEs of the Tn916/ICESt3/ICEBs1 family, a family of ICEs widespread in streptococci (11) and other Firmicutes (5).…”
Section: Resultsmentioning
confidence: 78%
“…This oriT recombination was likely mediated by the relaxase of the ICE, which is able to recognize and nick this sequence. Such oriT site-specific recombination has already been demonstrated for several canonical relaxases of plasmids (belonging to the MobF, MobP, MobC, and MobM families) (4,28,29) and has been suggested to occur in ICEs of the SXT/R391 family and for ICEclc (both encoding canonical relaxases of the MobH family) (30,31). This mechanism that enables creation of hybrid ICEs could thus also be mediated by relaxases of the noncanonical MobT family, which are related to rolling circle replication initiators and are found in ICEs of the Tn916/ICESt3/ICEBs1 family, a family of ICEs widespread in streptococci (11) and other Firmicutes (5).…”
Section: Resultsmentioning
confidence: 78%
“…To confirm this observation, we evaluated the role of the spores when mixed with different Cry toxins against C. elegans . To prevent the cross‐contamination of crystals with spores, we used a mutant strain YBT‐1517 to collect the spores, which was constructed based on YBT‐1518 to produce spores but no crystals (Wang et al ., ). The crystals of Cry6Aa and Cry5Ba were purified from recombinant B .…”
Section: Resultsmentioning
confidence: 97%
“…Bioinformatics analysis suggested that larger plasmid may be formed by fusion of smaller plasmids . The resolution and regeneration events of a native plasmid in B. thuringiensis also support this viewpoint .…”
Section: Discussionmentioning
confidence: 72%
“…Bioinformatics analysis suggested that larger plasmid may be formed by fusion of smaller plasmids [9]. The resolution and regeneration events of a native plasmid in B. thuringiensis also support this viewpoint [36]. For the plasmid with more than one minireplicon, whether all the minireplicons are functional for plasmid replication is another interesting topic.…”
Section: Discussionmentioning
confidence: 88%